Local Rainfall Variability - A Potential Bias for Bioecological Studies in the Central Amazon - Ribeiro,Maria de Nazaré Góes (1984)
Rainfall data registered betwe en 1910 and 1979 at Manaus confirm the existence of a dry season between June and November (monthly rainfall: 42-162mm) and a rainy season from December until May (monthly rainfall: 211-300mm). Annual precipitation amounted to 2105mm with about 75% of the rainfall recorded during the rainy season. Rainfall data collected over 12 months at eigth stations in the vicinity of and at Manaus are compared. Annual precipitation was lower in Inundation Regions (1150-2150mm) compared with Dryland Regions (2400-2550mm). Considerable differences are found in rainfall patterns (intensity, frequency and time of rainfall). This is also truefor neighbouring stations, even if data of a 11-year record period are compared. Thus, it is highly recommended that preciptation data for bioecological studies be collected at the study site.